Pengujian Kualitas Aplikasi Mobile Action Bank Aceh Dengan Metode Mccall - Bukhari, Fiona; Ilhadi, Veri; Fitria, Rahma (STMIK Sinar Nusantara, 2025)
ABSTRACTThe development of information technology encourages banking institutions to provide digital services, such as Mobile Banking applications. Bank Aceh released the Action Mobile application to facilitate practical financial transactions. However, there are stilla number of problems, such as servers often going down,account mutations are not updated, and bugs in the TopUpE-Wallet feature. This study aims to measure the quality of the Action Mobile applicationBank Aceh using the McCall method, which includes five factors: correctness,reliability, efficiency, integrity, and usability.The assessment was carried out through a quantitative approach by distributing a questionnairebased on McCall's indicators to 250 active user students. The data was analyzed using SPSS 24.0. The results show the correctness value of 81.88% (very good), reliability 63.50% (good), efficiency54.83% (quite good), integrity 43.23% (quite good), and usability 62.30% (good). In general the quality of the application is feasible, although the aspects of efficiencyand integrity still need to be improved. These findings are expected to be thebasis for improving Bank Aceh's digital services in the future.